Why do players purchase in mobile social network games? An examination of customer engagement and of uses and gratifications theory. Issue 3 (5th September 2017) - Huang, Taozhen; Bao, Zheshi; Li, Yan
Abstract : Purpose: The purpose of this paper is to explore the purchase intention in mobile social network games (M-SNGs) through a new perspective and discuss how to effectively promote players' payment. Design/methodology/approach: The author proposed a research model by integrating customer engagement (CE) and uses and gratification theory (U&G). Three dimensions of CE and three types of U&G were analyzed, respectively to explore the direct and indirect effects on purchase intention in M-SNGs. Online questionnaires were adopted to collect data, and 354 valid samples were analyzed by structural equation modeling approach. Findings: The findings show that hedonic gratification (entertainment) and social gratification (self-presentation) have significant indirect effects on players' purchase intention in M-SNGs through the mediation effects of CE, whereas this mechanism is not fully applied to utilitarian gratification (flexibility). Besides, three dimensions of CE are not independent, because absorption can indirectly affect vigor through dedication. Research limitations/implications: The findings suggest that hedonic gratification (entertainment) and social gratification (self-presentation) can trigger three dimensions of CE to stimulate purchase intentions in M-SNGs, and utilitarian gratification (flexibility) can also promote players' payment through absorption which is one dimension of CE. Some other theoretical and practical implications are also provided. Originality/value: This study is novel in exploring players' purchase intentions in M-SNGs by integrating CE and U&G. Meanwhile, the author also intends to reveal the relationships among the three dimensions of CE which are related to in-game purchase intention.